New Isothermic surfaces in S3 - V. Corro, Armando M. (2023)
In this paper, we consider a method of constructing isothermic surfaces in S3 based on Ribaucour transformations. By applying the theory to the flat torus, we obtain two family of complete isothermic surfaces in S3. One four-parameter family of complete isothermic surfaces that contains n-bubble surfaces inside and outside of the torus. We also get another four-parameter of complete isothermic surfaces which are Dupin surfaces. As aplication we obtain explicit solutions of the Calapso equation.